Advancing the understanding of Naegleria fowleri: Global epidemiology, phylogenetic analysis, and strategies to combat a deadly pathogen - Awadh Alanazi; Sonia Younas; Hasan Ejaz; Muharib Alruwaili; Yasir Alruwaili; Bi Bi Zainab Mazhari; Muhammad Atif; Kashaf Junaid (Journal of Infection and Public Health)
Naegleria fowleri is a rare but deadly pathogen that has emerged as an important global public health concern. The pathogen induces primary amoebic meningoencephalitis (PAM), a rapidly progressive and almost always fatal life-threatening brain infection. The devastating impact of N. fowleri and the high mortality rate underscores a deeper understanding and the development of innovative strategies to tackle this issue. Despite various studies that have been conducted on N. fowleri, a comprehensive review that integrates recent findings and addresses critical gaps in understanding remains lacking. This review provides a detailed overview of N. fowleri epidemiology, transmission dynamics, phylogenetic diversity, state-of-the-art diagnostic techniques, therapeutic approaches, and preventive measures. We identified 488 PAM cases globally, reported since 1962, with the highest numbers in the US, Pakistan, and Australia. A phylogenetic analysis of 41 N. fowleri ITS-1, 5.8S, ITS-2 region-based sequences showed genotypic diversity, with genotypes II and III being the most prevalent in Asia, North America, and Europe. Effective approaches to preventing N. fowleri transmission include applying free chlorine to water in storage tanks, taking precautions while swimming, and performing ablution with sterilized water (e.g., boiled or distilled) while avoiding deep inhalation of water, especially in regions with high water contamination. This review highlights the global impact of N. fowleri, future surveillance strategies, prompt diagnosis, potential therapeutic options, and vaccine development to prevent PAM outbreaks. It highlights the importance of joint government and public health efforts to combat this deadly pathogen.